2022
DOI: 10.1111/1462-2920.15876
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial volatile organic compounds induce adverse ultrastructural changes and DNA damage to the sugarcane pathogenic fungus Thielaviopsis ethacetica

Abstract: Due to an increasing demand for sustainable agricultural practices, the adoption of microbial volatile organic compounds (VOCs) as antagonists against phytopathogens has emerged as an eco-friendly alternative to the use of agrochemicals. Here, we identified three Pseudomonas strains that were able to inhibit, in vitro, up to 80% of mycelial growth of the phytopathogenic fungus Thielaviopsis ethacetica, the causal agent of pineapple sett rot disease in sugarcane. Using GC/MS, we found that these bacteria produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 133 publications
0
19
0
Order By: Relevance
“…The same study reported that the transverse and longitudinal septae completely disappeared in hyphae of Alternaria alternata, while conidiophores became vegetative and stunted in Cladosporium oxysporum (Chaurasia et al, 2005). Yet, other structural effects such as cell wall granulation, reduced number of mitochondria, destruction of organelles and internal cell darkening can be caused by VOCs, as it was observed in T. ethacetica (Freitas et al, 2022).…”
Section: Vocs Induce Critical Morphological Changesmentioning
confidence: 91%
See 4 more Smart Citations
“…The same study reported that the transverse and longitudinal septae completely disappeared in hyphae of Alternaria alternata, while conidiophores became vegetative and stunted in Cladosporium oxysporum (Chaurasia et al, 2005). Yet, other structural effects such as cell wall granulation, reduced number of mitochondria, destruction of organelles and internal cell darkening can be caused by VOCs, as it was observed in T. ethacetica (Freitas et al, 2022).…”
Section: Vocs Induce Critical Morphological Changesmentioning
confidence: 91%
“…( Ye et al, 2020 ). An increase in vacuolization processes (i.e., enlargement of vacuoles in mycelia, conidiophores or hyphae) has also been observed in some fungi inhibited by microbial VOCs or the respective synthetic compounds ( Chaurasia et al, 2005 ; Tenorio-Salgado et al, 2013 ; Giorgio et al, 2015 ; Medina-Romero et al, 2017 ; Huang et al, 2018 ; Freitas et al, 2022 ). According to Macías-Rubalcava et al (2018) , these changes can compromise the respiration of microorganisms and affect cell membrane permeability, as was observed in the endophytic fungus Hypoxylon anthochroum ( Macías-Rubalcava et al, 2018 ).…”
Section: Vocs Cause Several Molecular Changes On Phytopathogensmentioning
confidence: 92%
See 3 more Smart Citations